World Economic and Social Survey 2009 - United Nations (United Nations, 2009)
The separation in practice of climate change and development agendas has distorted the global debate on the two biggest policy challenges facing the international community. According to the Survey, an integrated approach based on the concept of sustainable development is urgently needed. It argues that mitigation and adaptation can move forward effectively only if they are part of a consistent development strategy built around a massive investment-led transformation along low-emissions, high-growth paths. The Survey also contends that a critical role must be played by developmental States able to mobilize public finance and build appropriate technological capacity.